Croato-Aegyptica Electronica - Database of the Egyptian Antiquities in Croatian Museum and Private Collections: Documentation Vs. Communication Approach - Tomorad, Mladen (Array, 2005)
The paper is based on International scientific and cultural project IT Croato-Aegyptica Electronica. In Croatia there are more than 4, 030 artifacts in 20 museums and unknown number in private collections (we presume around 1000). The basic aim of our project is to select relevant material presenting the cultural Egyptian connections with Croatia both in the form of institutions and private collections. It will include all Egyptian museum and private collections in Croatia from Predynastic periods until the Arab conquest of Egypt in 7th century A.D. Most of our artifacts came to museums in the second part of 19th century and first part of 20th century from various private collections. There are more than 3140 artifacts pertaining to the Egyptian civilization kept in the Archaeological Museum of Zagreb, the most important cultural and museum institution of the city of Zagreb and Croatia. There are also smaller or larger collections of Egyptian origin in other museums in Croatia. The most important collections according to the number of artifacts are to be found in the Mimara Museum in Zagreb (503), the Archaeological Museum of Dubrovnik – the Dubrovnik museums (197), the Archaeological Museum of Split (84), the Archaeological Museum of Istria in Pula (38), the Collection of the St. Euphemia monastery in Kampor on the island of Rab (14), the Archaeological collection of The Museum of Contemporary Art in Zagreb (11), the Archaeological Museum of Zadar (13), The Museum of Slavonia in Osijek (10), Museum of the City of Varaždin (6), the Franciscan monastery in Sinj (6), and in about dozen more town and regional museums with only one or two artifacts. Last year I published the book entitled Egypt in Croatia which includes the history and the most important information on each collection. With the help of custodians in the museums across the country my colleagues (I. Uranić, G. Zlodi, M. Gračanin, H. Gračanin, etc.) and I started to work on CAE project in November 2003. Our main goal is to make huge computer database of all artifacts that can be found in more than 20 museums collections in Croatia. From July 2004 CAE database is accessible on-line (www.croato-aegyptica.hr). We manage to analyze almost 800 artifacts from our museums since November 2003. One part of this database is right now on-line. We hope that in the beginning of next year 300-400 objects will be accessible through our Internet portal. In last few months we also prepared Croatian and English version of our web site (www.croato-aegyptica.hr) which is very educational and informative. The expanded possibilities lie behind the project Croato-Aegyptica Electronica – Date base of the Egyptian artifacts in Croatia so as a head of this scientific and cultural project I would like to inform everyone about our research and development of our project and CAE database.